Diabetes Melitus sebagai Gangguan Endokrin: Tinjauan Patofisiologi dan Pendekatan Diagnosis - Dini Gladis Saputri; Chika Amelia Putri; Cyntia Ramandani; Depi Sugesti; Ayuni Dwi Andini; Carmia Alysia Dina Haqiqi; Liss Dyah Dwi Arini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The endocrine system is a collection of hormone producing glands that regulate metabolism, growth, reproduction, and body balance. In glucose metabolism, one of the most common disorders is diabetes mellitus, a condition of chronic hyperglycemia caused by a lack of insulin or the body’s inability to respond to insulin properly. Type 1 diabetes is caused by autoimmune damage to the beta cells of the pancreas, while type 2 diabetes arises from a combination of insulin resistance and impaired insulin secretion. This problem not only disrupts blood glucose levels but also affects other organs such as the kidneys, eyes, and nerves. This study aims to explain the role of the endocrine system in the onset of diabetes mellitus, the hormonal mechanisms involved, and diagnostic approaches according to the latest guidelines. A proper understanding of the relationship between the two is important for early detection, therapeutic management, and long-term prevention.